Efficient, rapid, and regioselective bromination of anilines and phenols with 1-butyl-3-methylpyridinium tribromide as a new reagent/solvent under mild conditions - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Tetrahedron Letters, 2009)
1-Butyl-3-methylpyridinium tribromide, [BMPy]Br(3) proves to be a highly efficient, regioselective reagent/solvent for nuclear bromination of various anilines and phenols. The synthesis and characterization of the room temperature ionic liquid [BMPy]Br(3) (2) is described. The bromination was carried out in the absence of organic solvents and in most cases the only extraction solvent needed was water. The spent 1-butyl-3-methylpyridinium bromide (1) was easily recycled. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bromination; Ionic liquid; Regioselective; [BMPy]Br(3)